The Spread of Contaminants in Urban Drainage Networks Based on a Topological Analysis - Antonietta Simone; Alessandra Cesaro; Giuseppe Del Giudice; Cristiana Di Cristo; Giovanni Esposito; Oreste Fecarotta (Environmental Sciences Proceedings, 2022)
The present work proposes a methodology to model the diffusion of pollutants along urban drainage networks (UDNs) based on a topological analysis. The strategy is based on both the complex network theory and backtracking algorithms. The goals are to highlight the role of topology in the diffusion of pollutants and to simplify the computational effort compared with other methodologies without the need to solve optimization problems and to resort to hydraulic simulations. In particular, a new index called the node contamination index IC is proposed to evaluate the effect that the contaminant spill in each node has on the entire system. The strategy is presented as a support tool for both technicians and water utilities who must face the management of increasingly complex and unpredictable systems.